Enhancing student mastery of Subject-Verb Agreement (SVA) through SVnoes / Nursyuhada Zakaria ... [et al.] - Zakaria, Nursyuhada; Syed Abd Rahman, Sharifah Amani; Sa’adan, Nadzrah; Noorezam, Maisarah; Satanihpy @ Saidalvi, Aminabibi (Universiti Teknologi MARA, Kedah, 2023)
ESL learners should possess a strong grasp of grammar to help them to be able to use the target language effectively. One of the main problems that hinder students’ ability to be proficient in English is the mastery of subject-verb agreement. Hence, SVnoes is developed as a language game targeted for primary school students. It is inspired by the concept of Dominoes, where the language focus is on Subject-Verb agreement. There are 28 blocks which consist of various subjects and verbs. In groups of 4-6 people, each player takes turns to match the right subject with its suitable verb and write the phrase on a piece of paper. The game ends when all blocks are used up and the winner is determined by the highest total points collected in the game. Therefore, SVnoes promotes the use of correct SVA, enhances student communication skills, and encourages cooperation while playing the game. It incorporates a fun and indirect approach for students to learn and use SVA in a non-threatening environment. SVnoes is suitable to be commercialized as a teaching tool in language learning, such as a filler or reinforcement activity, in classroom and even home settings.